Magnetoliposomes incorporated in peptide-based hydrogels: towards development of magnetolipogels - Veloso, Sérgio Rafael Silva (2020)
A major problem with magnetogels is the encapsulation of hydrophobic drugs. Magnetoliposomes not only provide these domains but also improve drug stability and avert the aggregation of the magnetic nanoparticles. In this work, two magnetoliposome architectures, solid and aqueous, were combined with supramolecular peptide-based hydrogels, which are of biomedical interest owing to their biocompatibility, easy tunability, and wide array of applications. This proof-of-concept was carried out through combination of magnetoliposomes (loaded with the model drug curcumin and the lipid probe Nile Red) with the hydrogels prior to pH triggered gelation, and fluorescence spectroscopy was used to assess the dynamics of the encapsulated molecules. These systems allow for the encapsulation of a wider array of drugs. Further, the local environment of the encapsulated molecules after gelation is unaffected by the used magnetoliposome architecture. This system design is promising for future developments on drug delivery as it provides a means to independently modify the components and adapt and optimize the design according to the required conditions.